Pemetaan Status Kesuburan Tanah Sawah Menggunakan Sistem Informasi Geografis di Kecamatan Kerambitan Kabupaten Tabanan - Abni Sukma Br Tarigan; I Made Adnyana; Ketut Dharma Susila (Nandur, 2024)
The productivity of rice fields in the Kerambitan Subdistrict in 2019 was 5.97 tons/ha, and in 2020, it experienced a decrease to 5.65 tons/ha (a decrease of 5.4%). This occurred due to the diminishing soil fertility to support rice production. The purpose of this research is to determine the soil fertility status, limiting factors of soil fertility, provide guidance on soil fertility management, and create a soil fertility map. The research was conducted from February to May 2023 using survey and soil testing methods, categorized based on the Criteria for Assessing Soil Chemical Properties with parameters including soil fertility status: CEC, base saturation, organic carbon, total phosphorus, and total potassium. The results show two soil fertility statuses in the Kerambitan Subdistrict, namely moderate in Homogeneous Land Unit (HLU) II and V, and high soil fertility in HLU I, HLU III, HLU IV, and HLU VI. The limiting factor for soil fertility status in rice fields is organic carbon, which is classified as low in HLU II and V. Recommendations for soil fertility management include residue return after harvest and the addition of organic fertilizers to improve the soil fertility status of rice fields.